VACCINE FORMULATION: ADSORPTION OF Plasmodium falciparum MSP-1 PEPTIDE 1585 ON ALUMINIUM HYDROXIDE - TRUJILLO, Mary; SALAZAR, Luz M.; VALENCIA, Jesús (Vitae, 2011)
The Plasmodium falciparum merozoite surface protein 1 has been studied due to its potential to become a vaccine; likewise, the peptide 1585 which is located in the 42-kDa amino-terminal fragment induces protective immunity in primates. Despite the importance of antigen adsorption in the formulation and production of vaccines containing aluminium adjuvant, the protein fragment adsorption on aluminium hydroxide has not been thoroughly studied. Electrostatic attraction, hydrophobic interaction and ligand exchange have been identified as the major mechanisms involved in antigen retention on the adsorbent surface. Peptide 1585 was synthesized, and its solubility, adsorption on aluminium hydroxide, as well as its molecule release have been studied here. Results allowed us to raise a model for the adsorption and release of this peptide, which are important parameters to establish optimal conditions for peptideadsorbent interaction and, therefore, their response as a vaccine. Results also established the reversibility of such process due to the phosphate ion effect.Thus, this work provides a starting point for research works, leading to further development of vaccine formulations containing highly purified synthetic antigens adsorbed on aluminium adjuvant.